Multimodal disciplinary literacy in the senior physics classroom - Unsworth, Len; Tytler, Russell; Fenwick, Lisl; Humphrey, Sally; Chandler, Paul; Herrington, Michele; Pham, Lam (Multimodal Literacy in School Science, 2022)
This chapter describes research into the infusion of multimodal disciplinary literacy into pedagogy in senior physics classrooms in low socio-economic status school environments. The chapter begins by extending the discussion regarding the literacy demands of senior physics through analysis of textbooks, assessments and through evidence from teacher interviews and classroom observations. It then describes case studies of teachers working with multimodal literacy practices jointly planned with the research team, illustrative of the principles outlined in Chapter 6 in three areas: multimodal representational practices to explain electric circuits, joint construction of text and image in developing causal explanations of an electric motor and the building of graphical literacy resources in the topic of motion. The analyses of these case studies generate insights into (a) the diverse, yet distinctive ways physics knowledge involves transduction between and coordination of multimodal literacies across a range of genres; (b) the key features of pedagogies, aligned with M3S principles, that support student learning; and (c) the challenges and payoffs for teachers in enacting these pedagogies in the prevailing senior school science environment. Finally, we raise the question of the nature of a metalanguage that could be used to support teachers and students in developing these literacy practices. This chapter describes research into the infusion of multimodal disciplinary literacy into pedagogy in senior physics classrooms in low socio-economic status school environments. It begins by extending the discussion regarding the literacy demands of senior physics through analysis of textbooks, assessments and through evidence from teacher interviews and classroom observations. The chapter then describes case studies of teachers working with multimodal literacy practices jointly planned with the research team, illustrative of the principles. The Senior School Science (M3S) project involved working with groups of physics teachers to enact multimodal disciplinary literacy principles in a variety of topics. The experience is described through four case studies, dealing respectively with electric circuits, electric motor operation, describing motion and reporting experimental investigations. During the M3S project, these teachers became more aware of the way these discourses worked as fundamental to the shaping of learning and knowing.